Reconstructing the size of the African American population by age and sex, 1930-1990. - Preston, Samuel H.; Elo, Irma T.; Foster, Andrew (Demography, 1998)
A study was conducted to estimate the size of the African-American population by age and sex in five-year age groups from 1930 to 1990. A three-part strategy was used: For subjects born after 1935, the study followed the Census Bureau in using classical demographic analysis; extinct-generation estimates were used to estimate the size of cohorts born before 1895; and an age/period/cohort model of census counts was used for remaining cohorts. Findings indicated a strong support for the basic validity of Census Bureau estimates of census undercounts for African-Americans while extending estimates to new cohorts and periods. The findings are less consistent with an historical series prepared by Coale and Rives (1973).